2000
DOI: 10.1002/(sici)1521-4109(20000301)12:4<296::aid-elan296>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Cefepime at the Mercury Electrode

Abstract: The differential pulse polarography, DC-tast polarography and cyclic voltammetry behavior of cefepime was studied in phosphate buffer solutions (pH 1.6±12.1). In acidic media, a non reversible diffusion controlled reduction process involving two electrons takes place. The reduction mechanism is discussed. The linear relationship between peak current intensity and cefepime concentration allowed the differential pulse polarographic determination of cefepime over a wide concentration range, from 10 76 to 10 74 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Since most β-lactam antibiotics are eliminated from the body via urinary system cefalosporins have been frequently analyzed in urine by electrochemical methods [17,20,21]. In spite of the fact that the CFPZ is eliminated primarily by biliary excretion it can also be recovered from the urine [40,41].…”
Section: Determination Of Cfpz In Pathozone Milk and Urinementioning
confidence: 99%
See 1 more Smart Citation
“…Since most β-lactam antibiotics are eliminated from the body via urinary system cefalosporins have been frequently analyzed in urine by electrochemical methods [17,20,21]. In spite of the fact that the CFPZ is eliminated primarily by biliary excretion it can also be recovered from the urine [40,41].…”
Section: Determination Of Cfpz In Pathozone Milk and Urinementioning
confidence: 99%
“…Advantages of these procedures in analyzing the biological materials are their simplicity and rapidity, and often no other time-consuming separation procedure is necessary. Electrochemical techniques have been applied not only as a part of chromatographic detectors but also as an individual analytical method [17,18,19,20,21,22,23,24]. The β-lactam ring of cephalosporins is linked to a six-membered dihydrothiazine ring bearing substituents R 1 and R 2 in the side-chains at C-3 and C-7.…”
Section: Introductionmentioning
confidence: 99%
“…Determinations at mercury electrodes have been reported for cefadroxil ), cefatemet (Kapetanovic et al 2000a,b, Aleksic et al 2003, cefazolin (El-Desoky et al 2005), cefdinir (Jain et al 2007a(Jain et al ,b, 2008, cefepine ( Palacios et al 2000, Jimenez Palacios et al 2003, Kumar et al 2005, cefixime (Jain et al 2010), cefminox (Hilali Brought to you by | SUNY Binghamton Authenticated Download Date | 11/18/14 5:23 PM Table 2 Several electrochemical strategies complementing the direct voltammetric/amperometric measurements at macroelectrodes in analyte solutions reported in recent literature for determining pharmaceuticals.…”
Section: Voltammetric Methodsmentioning
confidence: 99%
“…The first one at peak potential (E p ) = À0.28 V (peak 1C) and the second at around E p = À0.45 V (peak 2C) vs. Ag/AgCl (KCl 3.0 mol L À1 ). This response is similar to that seen in previous works published using mercury electrode [25], but the reduction waves (peaks 1C and 2C) were displaced towards positive potentials (200 mV and 450 mV, respectively) when used the AgSAE. The less cathodic wave (peak 1C) is due to the reduction of the methoxymine group to methanol and the aminic cephalosporin derivative involving a complex process [29].…”
Section: Analysis Of Spiked Milk Samplesmentioning
confidence: 99%
“…Surveying the literature revealed that there are two electrochemical methods for determination of cefepime, both related to Palacios and coworkers [25,26]. This literature is related to the adsorptive stripping voltammetric determination of cefepime at the mercury electrode in human urine and cerebrospinal fluid, and differential pulse polarographic determination in serum.…”
Section: Introductionmentioning
confidence: 99%